A246: Epidemiological characteristics of injury among Chinese rowing athletes - Ma, H.; Deng, Y.; Mu, Z.; Zhou, X. (International Journal of Physical Activity and Health, 2026)
To develop a prevention program for rowing-related injuries, it is crucial to study the epidemiological characteristics of injury among Chinese rowing athletes. This study aimed to investigate the distribution and incidence of injuries among Chinese rowing athletes aged 12-24. A cross-sectional study was conducted among 207 rowing athletes using a rowing-specific questionnaire. The questionnaire survey asked for basic parameters, including sex, age, height, weight, rowing experience, training hours per day, training days per week, warm-up, and injuries associated with rowing over the past year. Injury rates per 1000 training hours and per 1000 training sessions were calculated. A total of 131 injuries were reported. The overall injury was 38.2% (male: 31.3%, female: 55.0%). The lower back was the most commonly injured site, accounting for 39.7%, followed by the knee (20.6%) and the shoulder (9.9%). Injury rate per 1000 training hours and per 1000 training sessions were 0.46 (95% CI: 0.38-0.54) and 2.16 (95% CI: 1.79-2.53), respectively. Among male rowing athletes, the injury rate per 1,000 hours was 0.35 injuries (95% CI: 0.239-0.461) for the =18 years group and 0.41 cases (95% CI: 0.26-0.55) for the >18 years group. The injury rate per 1,000 sessions was 1.43 injuries (95% CI: 0.98-1.89) for the =18 years group and 2.48 injuries (95% CI: 1.61-3.35) for the >18 years group. Among female rowing athletes, the injury rate per 1,000 hours was 0.42 injuries (95% CI: 0.28-0.57) for the =18 years group and 1.37 injuries (95% CI: 0.87-1.86) for the >18 years group. The injury rate per 1,000 sessions was 1.83 injuries (95% CI: 1.20-2.45) for the =18 years group and 7.85 injuries (95% CI: 4.99-10.70) for the >18 years group. Conclusions/Discussion: Among Chinese rowing athletes, lower back injuries were the most common, followed by knee injuries. Female athletes, especially those over 18 years old, were more susceptible to rowing-related injuries. As a retrospective study, it relies on the accuracy of the information provided by the athletes, which introduces a source of recall bias; furthermore, the smaller sample size of females over 18 years of age may lead to an overestimation of injury incidence. Future research should conduct prospective studies, controlling the sample size to ensure that the number of participants in each group is approximately equal. These findings have the potential to help precisely target the most at-risk sites and the athletes most vulnerable to injury.